(untitled) (Texas Journal of Engineering and Technology, 2024)
This article discusses the effectiveness and scope of steel and composite reinforcement, their advantages and disadvantages, as well as a comparison of their main characteristics. Describes tests to determine the combustibility of basalt reinforcement, in order to determine the possibilities of its application.